2006
DOI: 10.1097/01.sap.0000237565.39876.f9
|View full text |Cite
|
Sign up to set email alerts
|

Mastectomy Scar Histopathology of Limited Clinical Value

Abstract: This study assesses whether the routine submission of mastectomy scars for histologic examination at the time of delayed breast reconstruction is useful. A retrospective review was performed of all delayed breast reconstructions for breast cancer performed by a single surgeon over a 5-year period from January 2000 to December 2004. One hundred eighty-eight patients underwent delayed breast reconstruction during this period, and of these, 133 scars (1 patient had bilateral scars excised) were submitted for hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The timing of breast reconstruction postmastectomy varied significantly, from 2 to 168 months, averaging at 19.9 months. 1,3,[12][13][14][15][16][17] A comparison revealed that patients without recurrence underwent reconstruction sooner, at an average of 19.81 months, versus 39 months for those Takeaways Question: Does routine histological examination of mastectomy scars during delayed breast reconstruction contribute to patient outcomes? Findings: Our systematic review encompassed 11 retrospective observational studies, revealing a low recurrence rate of 0.19% in mastectomy scars during delayed reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of breast reconstruction postmastectomy varied significantly, from 2 to 168 months, averaging at 19.9 months. 1,3,[12][13][14][15][16][17] A comparison revealed that patients without recurrence underwent reconstruction sooner, at an average of 19.81 months, versus 39 months for those Takeaways Question: Does routine histological examination of mastectomy scars during delayed breast reconstruction contribute to patient outcomes? Findings: Our systematic review encompassed 11 retrospective observational studies, revealing a low recurrence rate of 0.19% in mastectomy scars during delayed reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Six patients (seven scars) experienced recurrence in their mastectomy scars. 1,6,15,17 Detailed information about the characteristics, histological diagnosis, and outcomes of the patients with recurrence is presented in Table 1. Adverse outcomes postreconstruction were reported in 83 patients (2.21%), 5,[12][13][14][15] as detailed at Supplemental Digital Content 1 (http://links.lww.com/PRSGO/D234).…”
Section: Resultsmentioning
confidence: 99%
“…Experts from other surgical fields such as orthopedic surgery and otolaryngology have arrived at conclusions similar to ours. 14,6,7,13,21–27,42,43 We anticipate this demonstration of the “low-yield” of routine pathology evaluation of benign hand lesions on a national level should promote a change in policy towards improving quality and efficiency of healthcare by institute guidelines to protect surgeons from practicing value-based care.…”
Section: Discussionmentioning
confidence: 97%
“…As only one scar had a “suspicious area of invasive ductal carcinoma” the authors concluded that routine histological examination of mastectomy scars may be of limited value in identifying recurrence. 11 Woerdeman et al examined 728 scars and did not find any evidence of metastatic or de novo tumor. With an estimated cost of € 50 ($ 65)/scar the authors concluded that “the pathologists may very well be the only one to benefit from such an examination”.…”
Section: Discussionmentioning
confidence: 99%
“…7, 11 The former group analyzed 133 mastectomy scars. As only one scar had a “suspicious area of invasive ductal carcinoma” the authors concluded that routine histological examination of mastectomy scars may be of limited value in identifying recurrence.…”
Section: Discussionmentioning
confidence: 99%